PARTICIPATORY MARINE SPATIAL AUDIT LESSONS FROM BEKASI REGENCY - Wahyudin, Yudi; Mahipal, Mahipal; Yusuf, Muhammad Arsjad; Riadi, Septa; Dewantara, Esza Cahya; Arkham, Muhammad Nur; Wahyudin, Muhammad Nur Hussein; Wahyudin, Muhammad Yuusuf; Wahyudin, Adinda Aisyah Puteri (Jurnal Segara, 2025)
Marine spatial management in coastal areas faces increasing challenges related to conflicts over space utilization and zoning violations that are often not detected at an early stage. This study aims to analyze the effectiveness of participatory marine spatial audits as an instrument for the early detection of conflicts and zoning violations, as well as to derive policy lessons from their implementation in Bekasi Regency. The study employs a participatory qualitative approach involving pentahelix stakeholders, including academia, government, the private sector, media, and coastal communities. The audit process was conducted through a collective assessment based on three main criteria: (i) conflict and risk, (ii) legality and compliance, and (iii) the suitability of the social-ecological system.  The audit results show an aggregate score of 3.08, categorized as “moderately compliant/requiring capacity building,” indicating that marine space utilization is relatively controlled but still requires strengthened governance. The participatory marine spatial audit proved effective in revealing latent conflicts, gaps between regulations and actual practices, and the influence of socio-economic factors on zoning compliance. Respondent characteristics, such as institutional background, age, education level, household size, and income level, were found to influence perceptions and audit assessment outcomes.  This study concludes that participatory marine spatial audits function not only as a technical evaluation tool but also as a mechanism for social learning and policy capacity building. Integrating marine spatial audits into local policy cycles has the potential to enhance early conflict detection, improve zoning compliance, and support sustainable and equitable marine spatial management.